The Role of Micro Finance in Empowering Women in Jaffna District - Yogendrarajah, R. (International Conference, Faculty of Management Studies & Commerce, University of Kelaniya., 2012)
Women mostly suffer from poverty in many developing countries. Sri Lanka, being one of the developing countries, and has been affected by the internal conflict over 30 years. Now, the post war development is carried out in the northern and eastern province of the country however, the war widows, disabled persons and female children are suffering from accessing education, health nutrition and employability. The micro finance facilities are provided for these people through NGOs, financial institutions and other government agencies to empower those people. This study reveals the role of the micro finance in empowering women in Jaffna District. The prime objective of this study is to look into the role of microfinance in empowering poor women. To find out the results, quantitative as well as qualitative methods were also employed in this study. A questionnaire which was self developed for a total of 77 respondents whom, however, only 66 completed the questionnaire. Further, three focus group discussions were conducted involving 18 women and in-depth interviews were carried out with another 12 in the selected DS Divisions of Jaffna, Nallur, Sandilipay and Kopay. The finding of this study was the improvement of the women’s self-confidence to work on their own and get better their lives. But, there is a little participation in the decision making in the household level or societal level. Further, the political empowerment is reflected by the ownership of assets and holding of political positions. Furthermore, the study also identified the challenges and difficulties that women face with Micro Finance Institutions (MFIs).
Keywords: Micro Finance; Women Empowerment; Economic empowerment; Socio-cultural empowerment; Political empowerment.